2017
DOI: 10.3390/ijms18051059
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin: The Pregnancy Hormone and More

Abstract: To thoroughly review the uses of human chorionic gonadotropin (hCG) related to the process of reproduction and also assess new, non-traditional theories. Review of the international literature and research studies. hCG and its receptor, LH/CGR, are expressed in numerous sites of the reproductive tract, both in gonadal and extra-goanadal tissues, promoting oocyte maturation, fertilization, implantation and early embryo development. Moreover, hCG seems to have a potential role as an anti-rejection agent in solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This glycoprotein hormone is responsible for development and seems to have evolutionary similarities to some pathways found in cancer cells [ 37 ]. In the same evolutionary context, hCG participates in promoting communication between the mother and foetus by enabling extremely invasive placentation [ 38 ].…”
Section: Placenta and Cancermentioning
confidence: 99%
“…This glycoprotein hormone is responsible for development and seems to have evolutionary similarities to some pathways found in cancer cells [ 37 ]. In the same evolutionary context, hCG participates in promoting communication between the mother and foetus by enabling extremely invasive placentation [ 38 ].…”
Section: Placenta and Cancermentioning
confidence: 99%
“…Therefore, BCB staining has been used to classify competent oocytes in mice [30,31], sheep [32], and cattle [33]. The human chorionic gonadotropin (hCG) surge triggers meiotic maturation in follicular oocytes and ovulation in various mammalian species during assisted reproductive technology (ART) programs [34]. The hCG mimics the action of luteinizing hormone (LH) and binds to LH receptors to trigger final maturation during last phases of folliculogenesis and thereby ovulation [34].…”
Section: Rosmentioning
confidence: 99%
“…Pituitary gonadotropin surge is a prerequisite for the initiation of meiotic maturation in oocytes [1,34]. Although hCG is frequently used as a surrogate for LH surge to induce ovulation in several mamma-lian species [34], its mechanism of action during achievement of meiotic competency remains ill understood. Our data suggested that almost 95% oocytes collected after 48 h PMSG surge were arrested at diplotene stage.…”
Section: Rosmentioning
confidence: 99%
“…Pituitary gonadotropin surge triggers EDA in follicular oocytes, a first step towards the achievement of meiotic competency [10,37]. Although hCG is commonly used to induce ovulation in several mammalian species [37], its mechanism of action during achievement of meiotic competency remains ill understood. Our data suggest that the majority of oocytes collected after 48 h PMSG surge were arrested at diplotene stage (approximately 95%).…”
Section: Rosmentioning
confidence: 99%
“…The induction of meiotic maturation and ovulation is achieved by giving human chorionic gonadotropin (hCG) surge in various mammalian species during assisted reproductive technology (ART) programs [37]. Due to structural and biological similarities to luteinizing hormone (LH), hCG binds to LH receptors [37] and induces reactive oxygen species (ROS) generation due to increased cell proliferation during the final stages of folliculogenesis [5,38]. Another source of ROS could be the inflammation generated due to follicular rupture during ovarian stimulation protocol.…”
Section: Introductionmentioning
confidence: 99%